Glycemia and Lipidemia in Term Newborns Correlate With Maternal Metabolism. (November 2019) - Oliveira, Hugo Razini; de Oliveira Toso, Beatriz Rosana Gonçalves; Guimarães, Ana Tereza Bittencourt; Viera, Cláudia Silveira; Grassiolli, Sabrina; Frizon, Bruna Juliana Zancanaro; Barreto, Grasiely Masotti Scalabrin; Conterno, Julia Reis; Minosso, Kamila Caroline
The present study characterized the plasma glycemic and lipid profiles in full-term newborn babies at birth and correlated these variables with growth markers and maternal clinical and metabolic conditions, to observe if maternal pregnancy conditions can influence metabolic programming in these newborn babies. Anthropometric and biochemical data were collected from 162 mother/newborn binomials at birth and at 6 months at a public hospital in Western Paraná State, Brazil. Samples of blood tests for glucose, insulin, total cholesterol, and triglycerides were obtained. Two classes of mothers/babies were statistically defined. The glycemic profiles in Class 1, at birth, were 63.0 ± 19.6 mg/dL and at 6 months 80.4 ± 10.6 mg/dL; in Class 2, at birth, they were 66.1 ± 20.8 mg/dL and at 6 months 78.2 ± 9.4 mg/dL. The triglycerides levels in Class 1 and Class 2, at birth, were 124.5 ± 47.8 mg/dL and 132.6 ± 60.2 mg/dL, respectively, and at 6 months they were 139.0 ± 51.5 mg/dL and 115.2 ± 39.9 mg/dL, respectively. Even though most of the pregnant women were overweight at the end of the gestation period, the anthropometric patterns found for babies followed the desirable standards. Furthermore, the average glycemic profile values were between the cutoff standards at birth and at 6 months; however, the triglycerides were above the expected values.